Peningkatan Pencapaian Target Produksi Kursi Lipat dan Kursi Susun Menggunakan Pendekatan Lean Manufacturing dan Line Balancing di PT XYZ - Nadila Eka Anggini; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT XYZ faces challenges in achieving the daily production targets of folding chairs and stacking chairs due to the accumulation of Work in Process (WIP), unbalanced workloads among workstations, and high waiting times during the production process. This study aims to identify waste and analyze production line balance to improve production efficiency. The research was conducted on the folding chair and stacking chair production lines using the Lean Manufacturing approach with Process Activity Mapping (PAM) and Line Balancing methods. PAM was applied to identify Value Added (VA), Non-Value Added (NVA), and Necessary Non-Value Added (NNVA) activities, while Line Balancing was used to evaluate workload distribution among workstations. The results indicate that the largest wastes occur in waiting and inventory activities, particularly in the chrome-plating process, which causes waiting times of up to three days. Improvements through workload balancing and the reduction of non-value-added activities were able to increase efficiency and improve production flow, enabling production targets to be achieved more effectively.